2021
DOI: 10.1111/ijfs.15370
|View full text |Cite
|
Sign up to set email alerts
|

An improved analytical method for determination of trans‐resveratrol and related stilbenes in grape skin by QuEChERS coupled with HPLC‐PDA‐MS

Abstract: Grape is a popular fruit crop that generates about one-fourth of total weight as pomace during winemaking and commercial juice production. However, a significant amount of resveratrol and related stilbenes is present in grape skin, and their effective isolation enables the production of functional foods. Herein, an improved analytical method for the determination of trans-resveratrol and related stilbenes in grape skin waste by QuEChERS method coupled with a high-performance liquid chromatograph-photodiode arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…This procedure was repeated 3 times and all the organic layers were pooled in a separatory funnel, followed by adding 5% sodium bicarbonate solution (pH 8-9) at a volume ratio of 1:1, washing until the organic layer became colorless, evaporating to dryness, dissolving in 0.5 mL of methanol, and filtering through a 0.22 µm membrane filter for HPLC analysis. Trans-resveratrol and cis-resveratrol in the grape skin were separated, identified, and quantified using a method described in a previous study [13].…”
Section: Extraction Of Resveratrol From Grape Skinmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure was repeated 3 times and all the organic layers were pooled in a separatory funnel, followed by adding 5% sodium bicarbonate solution (pH 8-9) at a volume ratio of 1:1, washing until the organic layer became colorless, evaporating to dryness, dissolving in 0.5 mL of methanol, and filtering through a 0.22 µm membrane filter for HPLC analysis. Trans-resveratrol and cis-resveratrol in the grape skin were separated, identified, and quantified using a method described in a previous study [13].…”
Section: Extraction Of Resveratrol From Grape Skinmentioning
confidence: 99%
“…Then, both the size and shape of the resveratrol nanoemulsion were obtained. Also, the encapsulation efficiency was determined by collecting a portion (100 µL) of the resveratrol nanoemulsion and diluting it with deionized water 10 times, followed by pouring into a centrifuge tube containing a 3 kDa dialysis membrane, centrifuging at 12,000× g for 20 min (25 • C), collecting the lower layer (200 µL) containing free resveratrol, evaporating to dryness, and dissolving in methanol for HPLC analysis of resveratrol [13]. Then, the encapsulation efficiency of resveratrol was obtained by using a formula described in a previous study [14].…”
Section: Characteristics Determination Of Resveratrol Nanoemulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research studies have associated EA with beneficial pharmacological activities, above all against in diabetes, cancer, neurodegenerative disorders and cardiovascular diseases, and it has attracted great interest recently [13][14]. Many research studies have demonstrated the many biological functions of RES, including antioxidant, antiinflammation, anti-cancer, anti-diabetes, anti-obesity, anti-microbial, anti-aging, cardio protection, and neuroprotection [15].…”
mentioning
confidence: 99%